Jurisprudential Analysis of Reserved Advantages Clauses Agreed in the Spanish Collective Bargaining - Ferradans Caramés, Carmen (2016)
In this article the author develops a jurisprudential analysis of the right to negative freedom of association, as an essential part of the right to freedom of association, and how certain agreements, concluded within the framework of collective bargaining, contain provisions that go against the principle non-discrimination. Such agreements are declared null and void, and sometimes are admitted and incorporated into the constitutionality and legality. Based on typical cases will be discussed in which situations the agreements concluded by unions violate the right to negative freedom of association of the unaffiliated and become a discriminatory act and an unjustified pressure to join a union.